Hubungan Persepsi Lingkungan Pembelajaran dengan Strategi Pembelajaran Mahasiswa Program Studi Pendidikan Dokter Universitas Jambi - Nyimas Natasha Ayu Shafira; Anwar Jusuf; Setyawati Budiningsih (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: Students' perceptions toward learning environment may influence the use of students' learning strategies. In medical education, the students are expected to implement deep approach. Therefore, students' learning environment should be able to direct the students to learning by using deep approach. The purpose of the research was to investigate the relationship between students' perception about learning environment, students' learning strategies, among medical student in Jambi Medical School (UNJA)Method: This research employs cross sectional design from April to June 2012. The samples were 198 respondents who were students in semester 2, 4 and 6. The date of the perception about the learning environment and learning strategies was adopted from questionnaires from Dundee Ready Educational Environment Measure (DREEM) and The Revised two Factor study process Questionnaire (R-2F-SPQ).Results: The study showed that 80 percent of the students have positive perception regarding learning environment in UNJA. More than half of the students applied deep approach. There was significant relationship between students' perceptions about learning environment with learning strategies used by the students (p = 0,001). There was a tendency that better students' perception toward learning environment made students prefer deep approach.Conclusion: There is significant relationship between students' perceptions about learning environment with learningstrategies used by the medical students of PSPD Jambi.